MEASUREMENT OF INTANGIBLE ASSETS IN RECOVERY AREAS AND OPERATION OF NATURAL RESOURCES - Gâf-Deac, Ioan I.; Valeca, Cristina Monica; Gurgu, Elena; Bărbulescu, Adrian (Annals of Spiru Haret University. Economic Series, 2017)
The paper shows that to date, intangible assets are considered "goods" and as such, the practice of classical accounting consider intellectual capital in the same category of "goods equivalent / similar to those visible / tangible". From research that literature on measuring knowledge assets / intellectual capital, both in Romania and worldwide, is not large enough and does not provide finite significant "strong" on classifications semantic of the content and quality issues in the field. The book titled New Economy between knowledge and risk – Infomin Ed., Deva, 2010 (www.infomindeva.ro) (ISBN 978-973-7646-11-8), (Ioan I. Gâf-Deac) presents systematization and classification of original models and methodologies for measuring knowledge assets, intellectual capital in socio-economic sciences, and as such, in this present article resorting to the extension applied to formalizing measurement of intangible assets in areas operation and exploitation of natural resources.